2020
DOI: 10.3390/su12031250
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Soil Microbes Related with Carbon and Nitrogen Cycling after Long-Term CO2 Enrichment in a Typical Chinese Maize Field

Abstract: Elevated atmospheric CO 2 concentration (eCO 2 ) has been the most important driving factor and characteristic of climate change. To clarify the effects of eCO 2 on the soil microbes and on the concurrent status of soil carbon and nitrogen, an experiment was conducted in a typical summer maize field based on a 10-year mini FACE (Free Air Carbon Dioxide Enrichment) system in North China. Both rhizospheric and bulk soils were collected for measurement. The soil microbial carbon (MBC), nitrogen (MBN), and soil mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 62 publications
(67 reference statements)
1
11
0
Order By: Relevance
“…A probable explanation for the high prevalence of fungi in our pots is that soil pH value of 4.2 in this study was most favorable for growth and survival of the fungus. Other study has been shown that pH has a decisive influence on fungal biomass [4,72]. Previous studies on the effects of eCO 2 on fungal community structure have documented a variety of responses, from no effect [66,73] to significant separations among communities [31,74,75].…”
Section: Changes In Fungal Community Structure Under Ecomentioning
confidence: 97%
See 1 more Smart Citation
“…A probable explanation for the high prevalence of fungi in our pots is that soil pH value of 4.2 in this study was most favorable for growth and survival of the fungus. Other study has been shown that pH has a decisive influence on fungal biomass [4,72]. Previous studies on the effects of eCO 2 on fungal community structure have documented a variety of responses, from no effect [66,73] to significant separations among communities [31,74,75].…”
Section: Changes In Fungal Community Structure Under Ecomentioning
confidence: 97%
“…Plant photosynthesis is a highly efficient and low-cost method of CO 2 absorption that might significantly affect soil ecosystems [2]. However, little research on the microbial community in the rhizosphere soils of greenhouse plants has been performed, even though greenhouses are widespread [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The error of measured data in eCO 2 during the summer maize growth period was controlled for within 20 ppm on more than 85% of days. The detailed description of this FACE experiment has been reported by Diao et al [47] and Han et al [48].…”
Section: The Experimental Design and Field Managementmentioning
confidence: 99%
“…eCO 2 stimulates the C flow from plant roots to soils and promotes microbial activity. Greater utilization of additional C resources and root secretions [ 20 , 21 ], a significantly higher abundance of genes associated with C and N cycling [ 22 ] and increased enzyme activity [ 23 , 24 ] indicate rapid nutrient cycling and the stimulation of microbial activity under eCO 2 . Unfortunately, the isotope pulse-labeling technique used in previous studies was less stable than the steady isotope labeling technique, and little research has focused on the effects of various CO 2 concentrations, especially in greenhouse soil ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Soils managed under plastic tunnel greenhouses, which are widely used in fruit and vegetable plantations and characterized by lower pH levels and nutrient-poor conditions under longer planting durations, have rarely been studied under various CO 2 treatments [ 22 , 25 , 26 ]. The soil microbial community composition in the rhizosphere soils of tomato changed insignificantly under various CO 2 treatments in our previous study [ 27 ].…”
Section: Introductionmentioning
confidence: 99%